Differences in metabolic stress using a breathing restrictive mask compared to hypobaric hypoxia during cycling at a matched workload - Bellovary, B. N.; Wells, A. D.; Fennel, Z. J.; Houck, J. M.; Millender, D. J.; Bourbeau, K. C.; Mermier, C. M. (Journal of Science in Sport and Exercise, 2021)
Purpose: The Elevation Training Mask (ETM) has been assessed for its impact on exercise performance using acute and training protocols. Although the ETM is widely available to consumers, little research exists for validation of the ETM mask settings. Therefore, the purpose of this study was to compare physiological responses during exercise for the ETM mask settings against moderate hypobaric hypoxia. Methods: Nine participants living at moderate altitude (1600-1650 m) rested (10 min) and cycled in hypobaric hypoxia simulating 2743 m (ALT), in hypobaric hypoxia simulating 1829 m with the ETM set to 914 m (ALT + ETM), and with the ETM set to 2743 m (ETM) in a randomized order. Participants cycled for 20 min at 60% VO2max as determined by a maximal exertion test (VO2max) at baseline altitude. Oxygen consumption was measured throughout each test. Results: There were no differences between conditions at rest. Repeated measures ANOVA showed the ALT condition elicited significantly greater VO2 compared to the ETM condition and 60% VO2max at baseline altitude (P < 0.05). Conclusion: When cycling at a matched workload, the exercising VO2 was higher in the ALT condition than at the ETM mask setting of 2743 m and exercising VO2 during the ETM condition was similar to 60% VO2max at baseline altitude. The results of this study indicate that the ETM did not produce additional metabolic stress compared to hypobaric hypoxia during steady-state exercise in moderate-altitude living individuals.